2015
DOI: 10.1590/1982-021620151765815
|View full text |Cite
|
Sign up to set email alerts
|

Fonoterapia em grupo e sua eficácia para tratamento da disfonia: uma revisão sistemática

Abstract: RESUMO: O objetivo deste estudo foi realizar uma revisão sistemática sobre terapia vocal de grupo e seus efeitos em pacientes com disfonia. O estudo é do tipo revisão sistemática da literatura. A pesquisa foi realizada a partir da associação dos descritores (também em inglês) "terapia de grupo", "voz" e "disfonia", nas bases de dados Scientific Eletronic Library Online (SciELO), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Medical Literature Analysis and Retrievel System Online (Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
(25 reference statements)
0
7
0
8
Order By: Relevance
“…Table 4 shows the modification of URICA-Voice questionnaire items by comparison of the responses given by the patients in the pre-and post-therapy stages. The items on the questionnaire that showed the most significant change in the responses between the two stages were: 3,16,17,19,21,24, and 28. In each of these questions, post-therapy responses had a number equal to or significantly less than the pre-therapy stage among patients with behavioral dysphonia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4 shows the modification of URICA-Voice questionnaire items by comparison of the responses given by the patients in the pre-and post-therapy stages. The items on the questionnaire that showed the most significant change in the responses between the two stages were: 3,16,17,19,21,24, and 28. In each of these questions, post-therapy responses had a number equal to or significantly less than the pre-therapy stage among patients with behavioral dysphonia.…”
Section: Resultsmentioning
confidence: 99%
“…A recently published literature review examined group vocal therapy and its effects in patients with dysphonia (3) . After considering their limitations and suggestions, the authors found most of the selected studies indicated group vocal therapy to be effective at all ages, and not only promoted vocal health, but also prevented dysphonia (3) . Unfortunately, there are few studies, in the literature, that have evaluated the patient's stage of readiness to speech therapy in the voice area (10,15,22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionals have highlighted that group therapy is a strong method of intervention in the treatment of dysphonia as it allows for an interactive dynamic session. 26 Furthermore, the advantage of the group over individual interventions includes knowing that others share the same difficulties and challenges and promotes support within the group. 27 Thus, this intervention approach presumptively had a positive effect on the favorable outcome of the voice care program among the primary school teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Group therapy has been quite an effective strategy for treating the voice 34 , since it has given patients the ability for self-perception and for identifying vocal symptoms, as well as strategies for resolving voice problems. Thus, working together and sharing with other people who present the same problem or some other similar one makes patients develop more strategies to confront dysphonias and makes them more active in the rehabilitation process 35 .…”
Section: Discussionmentioning
confidence: 99%